The growth and delivery of mesenchymal and limbal stem cells using copolymer polyamide 6/12 nanofiber scaffolds - Holan, Vladimir; Javorkova, Eliska; Trosan, Peter (Methods in molecular biology (Clifton, N.J.), 2013)
The injured or otherwise damaged cornea is healed by limbal stem cells (LSC). If the limbus where LSC reside is also damaged or nonfunctional, the cornea cannot heal properly and this defect leads to impaired vision that can result in blindness. The only way to treat total LSC deficiency is by transplantation of limbal tissue or a transfer of LSC. Recently, mesenchymal stem cells (MSC) have been shown as another promising source of stem cells for corneal healing and regeneration. Here, we describe a protocol for the use of polyamide 6/12 nanofiber scaffolds for the growth of MSC and LSC, and for their transfer onto a mechanically damaged ocular surface in the experimental mouse model.
Keywords: Nylons; tvar buňky; Mesenchymal Stem Cells; separace buněk; Antigens, CD; CD antigeny; myši inbrední BALB C; buněčné kultury; Mesenchymal Stem Cell Transplantation; nylony; Adult Stem Cells; Mice, Inbred BALB C; Limbus Corneae; kultivované buňky; Animals; lidé; nanovlákna; Cell Separation; Humans; zvířata; Cell Culture Techniques; Tissue Scaffolds; Nanofibers; myši; Cells, Cultured; tkáňové podpůrné struktury; Mice; transplantace mezenchymálních kmenových buněk; Cell Shape; dospělé kmenové buňky; limbus corneae; mezenchymální kmenové buňky